2022
DOI: 10.1093/schbul/sbac035
|View full text |Cite
|
Sign up to set email alerts
|

The Time is Ripe for a Consensus Definition of Clinical Recovery in First-episode Psychosis: Suggestions Based on a 10-Year Follow-up Study

Abstract: Objectives A consensus definition of clinical recovery in first-episode psychosis (FEP) is required to improve knowledge about recovery rates in this population. To propose criteria for a future consensus definition, this study aims to investigate rates of clinical recovery when using a standard definition (full psychotic symptom remission and adequate functioning for minimum one year) across both affective and nonaffective FEP groups (bipolar spectrum and schizophrenia spectrum disorders). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
3
12
0
Order By: Relevance
“…Clinical recovery (CR) is defined as stable symptom remission in the context of regained function over a sustained period of at least six months by some-and up to twenty-four months by other criteria (11)(12)(13). Recovery rates in FEP vary between 10-35%, depending on the definition of recovery and the length of the follow-up period (14,15). Long-term CR is predicted by good premorbid functioning, lower levels of psychopathology at baseline, and a shorter duration of untreated psychosis (DUP) (14,(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical recovery (CR) is defined as stable symptom remission in the context of regained function over a sustained period of at least six months by some-and up to twenty-four months by other criteria (11)(12)(13). Recovery rates in FEP vary between 10-35%, depending on the definition of recovery and the length of the follow-up period (14,15). Long-term CR is predicted by good premorbid functioning, lower levels of psychopathology at baseline, and a shorter duration of untreated psychosis (DUP) (14,(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Adequate functioning was de ned as part-time (≥40%) work or study, or comparable functioning, independent living and having a close friend/con dant (29).…”
Section: Participantsmentioning
confidence: 99%
“…While subsequent studies have operationalized objective recovery somewhat differently (see, e.g., Åsbø et al, 2022), the desire to understand and improve long-term outcomes is strong. Molstrom et al (2022) recently reported a systematic review and meta-analysis with metaregression on prospective studies of schizophrenia having at least 20 year follow-up data ( n = 1,027).…”
Section: Growth Of the Recovery Movementmentioning
confidence: 99%